METODE RASULULLAH SAW DALAM PENYAMPAIAN HADITS KAWMAWAIN: Studi Hadits Tahlili Dengan Perspektif Suggestopedia - Permana, Dede (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2022)
It’s a good pride for some people if they get an excellent teaching carefully from their teachers, especially if the values are delivered in a good way as well. This research wants to explore more qualitatively and descriptively about the methods and words that the Prophet Muhammad PBUH chosed in giving this parable for the people who in the every single day at the morning goes to the mosque to read several verses from the Qur'an. Furthermore, the analysis will be viewed from suggestopedia's perspective. This discussion can conclude that a learning method that has been implemented well and effectively will be acceptable to the listener with maximum quality of understanding. The hope is that it will be practiced as best as possible as the output of the value transformation activity.